Quantification of surfactant proteins in tears of patients suffering from dry eye disease compared to healthy subjects - Posa, Andreas; Sel, Saadettin (Annals of anatomy, 2018)
Purpose: To quantify and compare the amounts of surfactant proteins SP-A, SP-B, SP-C and SP-D in the tear fluid collected from patients with dry eye syndrome and from individuals with a healthy ocular surface. Methods: Schirmer strips were used to collect tear fluid from both eyes of 241 volunteers (99 men, 142 women; age range: 18–87 years). Dry eye syndrome was diagnosed by ophthalmologists in 125 patients, whereas the healthy control group comprised 116 individuals. The total protein concentration was determined via Bradford assay. The relative concentration of surfactant proteins SP-A through -D was measured by enzyme-linked immuno-sorbent assay (ELISA). Results: The mean relative concentrations of SP-A, SP-C and SP-D were significantly higher in the dry eye group as compared to the healthy controls (p < 0.05, one-way ANOVA). SP-B was also detected at a higher concentration in the dry eye group, but the difference to the control group was not statistically significant. Conclusions: The upregulation of SP-A and SP-D in the dry eye group is probably related to these proteins’ known antimicrobial and immunomodulatory effects at the ocular surface. It may represent a pathophysiological response to the inflammatory condition of the ocular surface in dry eye. The upregulation of SP-B and SP-C may represent an effort of the lacrimal system to reduce surface tension and thus to counteract the increased tendency of the tear film to tear in dry eye.
Available online 24 December 2017
Gesehen am 24.08.2018